1975
DOI: 10.1128/jvi.16.5.1296-1307.1975
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure of Uukuniemi virus

Abstract: Uukuniemi virus, grown in chicken embryo fibroblasts, has been studied by electron microscopy using negative staining, thin sectioning, and freezeetching techniques. The spherical virus particle measures about 95 nm in diameter. Its envelope consists of a 5-nm thick membrane covered by 8-to 10-nm long surface projections. These are composed of two polypeptide species of about the same size. Both of them can be removed by digestion with the proteolytic enzyme thermolysin except for a small fragment. The enzyme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…UUK virus displayed the same morphological surface structure (Fig. 5E) as described before (52). The VLPs produced by transfection showed a particle morphology that was identical to that of the UUK virus particles (Fig.…”
Section: Generation Of Infectious Vlps For Uuk Virussupporting
confidence: 68%
See 1 more Smart Citation
“…UUK virus displayed the same morphological surface structure (Fig. 5E) as described before (52). The VLPs produced by transfection showed a particle morphology that was identical to that of the UUK virus particles (Fig.…”
Section: Generation Of Infectious Vlps For Uuk Virussupporting
confidence: 68%
“…The lipid envelope contains glycoproteins that form characteristic projections that can be visualized efficiently by electron microscopy. The projections are clustered to form hollow cylindrical units arranged in a icosahedral surface lattice (hexons and pentons) with a T12 symmetry (52). Supernatants from UUK virus-infected cells and cells transfected with only the pUUK-G N /G C plasmid or with pUUK-G N /G C together with M-CAT, pUUK-L, and pUUK-N were collected, fixed with glutaraldehyde (0.7%) to preserve the surface morphology, concentrated by ultracentrifugation, and subjected to negative staining and electron microscopy ( Fig.…”
Section: Generation Of Infectious Vlps For Uuk Virusmentioning
confidence: 99%
“…We recently demonstrated that for UUK virus, the glycoproteins alone are sufficient for VLP formation, thus excluding a role for the nucleoprotein in the budding process (30), which was also confirmed in the present study. It was previously suggested that the glycoproteins are responsible for the structural stability of the virus, since spikeless particles were found to be highly deformed (44). We similarly suggest that the G N /G C proteins by themselves can generate particles and bud into the Golgi complex, and also the ER-Golgi intermediate compartment (13), when a critical glycoprotein concentration is reached.…”
Section: Discussionsupporting
confidence: 58%
“…Negative staining of samples containing UUKV-RED was performed with phosphotungstic acid at pH $7.4 as previously described (von Bonsdorff and Pettersson, 1975). For thin-section EM, after exposure to virus (moi $100), cells were fixed and treated as previously described (Johannsdottir et al, 2009).…”
Section: Electron Microscopymentioning
confidence: 99%